Development of Antipodal Vivaldi Antenna with Modified Electromagnetic Band Gap Structures for Ultra-Wideband Indoor Applications - Saidu Adamu, Abubakar (Universiti Malaysia Sarawak (UNIMAS), 2019)
Ultra-wideband frequency spectrum has emerged for both commercial and industrial wireless communication applications after the commercial licensing of the UWB frequency spectrum covering 3.1 – 10.6 GHz by the federal communication commissions (FCC) in February 2002 which has led to quite a number of UWB antenna designs being proposed in both the academia and the industry. UWB antennas such as log-periodic, TEM horn, fractal, spiral, bow-tie, conical and Vivaldi antennas have being investigated and proposed. Due to desirable electrical features of planar and simple structure, light weight and low profile, symmetric beam in both radiating planes, conformity with mounting host surfaces among others, the antipodal Vivaldi antenna have enjoyed more competitive advantage compared to other UWB antennas which are not lightweight and are non-planar. However the antipodal Vivaldi antenna despite these advantages, still suffers from drawbacks such as tilted beam, low or inconsistent directivity and gain. Moreover, within the specified 3.1 – 10.6 GHz UWB frequency spectrum also exist other narrow band wireless technologies including IEEE 802.16 WiMAX standard at 3.5 GHz and the IEEE 802.11a WLAN standard at 5.5 GHz, which might cause possible electromagnetic interference to the UWB applications. In this study, therefore two techniques are employed based on incorporating an exponential slot edge corrugation on the radiating flare of the antenna and loading a high permittivity dielectric director in the flared aperture of the antenna to improve its performance. Likewise, a modified EBG structure is designed and incorporated in to a novel double-layered AVA to notch the two wireless bands at 3.5 GHz and 5.5 GHz. CST MWS is used for the simulation and a Rohde & Schwarz ZNB40 Vector Network Analyzer (VNA) for fabricated prototype measurement. The two techniques employed in this thesis achieved measured impedance bandwidth and highest measured gain improvement of 14.23% (2.74 GHz to 2.35 GHz) and 56% (3.62 dB to 5.65 dB) as well as 1.46% (2.74 GHz to 2.70 GHz) and 77% (3.62 dB to 6.42 dB) respectively over the conventional AVA. The structural modifications employed on the AVA in this thesis results in a significant improvement in the performance of the AVA with respect to the antenna gain and directivity and correcting the phase error and beam tilting in the E-plane at higher frequencies. Additionally, with simple structure, symmetric and stable end-fire radiation pattern over its operating band, the proposed antenna has proved to be a good choice for band-notch operation in UWB system operation without the need for extra circuitry to filter out the band of frequencies that might cause potential interference.